Is calcium a concern in neonates undergoing phototherapy? - Sreeram, S.; Srinivas, M.; Sridhar, N.L. (European Journal of Pediatric Dermatology, 2018)
Neonatal jaundice is one of the most common problems that can occur in the newborn. Hypocalcemia during phototherapy has been reported in literature. Our aim was to look the effect of phototherapy on ionized calcium levels before and after phototherapy in otherwise healthy term and late preterm (35 to 37 weeks) neonates. The study group included 50 neonates. Measurement of serum ionized calcium levels was done before and at the end of phototherapy. At the end of phototherapy in the study group a significant fall in calcium level in 64% of term and 76% of late preterm neonates was observed. However, almost all except one remained asymptomatic. Serum calcium levels should be assessed in neonates treated with phototherapy.